Marina Turiman Bakery: strengthening the brand equity among Maran community - Shaari, Hasnizam; Perumal, Selvan; Abdul Murad, Safwan Marwin (2021)
The bakery industry plays a significant role in economic development in Malaysia. The industry itself consists of many players ranging from giant multinational companies to small stand-alone enterprises that complement each other. Huge companies are known for systematic production, advanced supply chain, and well-formulated marketing activities, while small enterprises struggle to remain resilient in the hostile market. Literature review stated that small and medium enterprises were identified as incapable of strategizing their marketing strategies accordingly, especially when it comes to branding practices. This case study is based on a stand-alone SME bakery in Maran, Pahang. Marina Turiman, the owner of Marina Turiman Bakery had changed her business from Make Up Bakery to Marina Turiman Bakery to strengthen her brand presence among Maran community. Besides, the owner had repositioned her product offerings as ‘luxury taste bakery’ and had registered with MYIPO under the logo ‘Mariman’. Marina Turiman, UUM graduate and a disabled person had a strong determination to succeed in her business. She committed to offering high-quality bakery products at an affordable price to fulfill the local community's need. Within five years, she managed to open a new outlet –garden café concept at Dataran Tasik Maran, Pahang to cater overwhelming demand and changing lifestyle of the local community. Marina Turiman did not employ any intermediaries and highly depended on social media (such as Facebook, Youtube, and Tiktok) to promote her business. Besides, she also actively promoted her brand via traditional media such as brochures to create awareness and remind customers. She continuously offered sales promotions such as special discounts and free coupons to stimulate try and repeat purchases and, more importantly, appreciate her loyal customer. This case study is suitable for undergraduate programs such as Marketing Management, Brand Management, and Marketing Seminar. Students would be able to assess how stand-alone SME Bakery strengthening its brand equity